Utilization of indigenous phosphate-solubilizing bacteria to optimize the use of coal fly ash for increasing available-P in an Ultisol - Budi Purnomo; Novi Rahmawati Sutopo; Yulia Nuraini (Journal of Degraded and Mining Lands Management, 2021)
Coal fly ash (CFA) is a coal-burning by-product containing macro and micronutrients, and it is the potential material for improving available P in Ultisols. Phosphate-solubilizing bacteria (PSB) play a role in phosphorus solubilization. This study aimed at elucidating the potential use of phosphate-solubilizing bacteria to optimize the use of coal fly ash for increasing soil available P. This study was conducted in two stages, namely isolation of indigenous PSB from an Ultisol and application of the PSB and CFA to improve soil available P. Five indigenous PSB isolated from the soil had the ability to dissolve phosphate. Isolate B5 could dissolve 9.89 ppm P and had a 99.57% closeness to Pseudomonas stutzeri. The application of 20 and 40 t CFA ha-1 increased the soil pH by 4.2% and 7.2%, respectively. Increasing the dose of CFA decreased the content of available P by 50.6%. However, the combination of PSB and 20 t CFA ha-1 increased soil available P, plant growth, plant dry biomass, and P-uptake by plant.